Pembatalan Putusan Badan Arbitrase Nasional Indonesia Berdasarkan Pasal 70 Undang-Undang Nomor 30 Tahun 1999 tentang Arbitrase dan Alternatif Penyelesaian Sengketa Ditinjau dari Sifat Final dan Mengikat: Studi Kasus Putusan Nomor: 104 B/Pdt.Sus-Arbt/2019 - Diah Yulinda wulandari; Maman Suparman (Sekolah Tinggi Ilmu Hukum Prof Gayus Lumbuun, 2024)
The application of the provisions of Article 70 of Law Number 30 of 1999 has resulted in inconsistent interpretations and no firm rules. On the other hand, BANI's decision is final and binding. However, it is not uncommon for parties who are dissatisfied with the arbitration award to file a lawsuit to annul the BANI decision to the district court. This legal research is classified as normative juridical research which aims to examine legal certainty based on literature studies (documents or library research), case approaches, and applicable positive law. The results of this thesis research show that the cancellation of BANI's decision through Decision Number: 104 B/Pdt.Sus-Arbt/2019 was based on allegations that it contained elements contained in Article 70 of Law Number 30 of 1999, namely that after BANI's decision was taken, documents were found that decisive, which was deliberately hidden by Shimizu Corporation and PT. Hutama Karya. Thus, the annulment of the BANI decision Number 854/V/ARBBANI/2016, clearly and clearly includes the reasons for the cancellation of the arbitration award and the judge's considerations regarding the annulment of the BANI Decision through Decision Number: 104 B/Pdt.Sus-Arbt/2019, of the opinion that the claim proposed by Shimizu Corporation and PT. Hutama Karya to BANI, it was proven that there were several documents that were not submitted by Shimizu Corporation and PT. Hutama Karya, however, if the document is submitted, BANI's decision will be different or at least it will not grant the demands of Shimizu Corporation and PT. Hutama Karya in whole or in part, in this case, includes claims regarding fluctuations in the rupiah exchange rate.